Development of a chemical-free technology for the control of bio-fouling on glass and polystyrene surfaces - Tan, Gabriel Hseng Ho. (2013)
Research effort has been dedicated to develop new chemical-free technology for control and mitigation of membrane bio-fouling. In this report, the surface properties of glass and polystyrene materials and their relationship to the mass of biofilm formed are being investigated. Different parameters, such as the type of contact surface, the duration of air bubbling treatment time and the stability of microbubbles (MBs) in liquid, were varied and documented to determine the most efficient way of cleaning the bio-fouled surfaces. It is important to acknowledge that sole usage of MBs as a cleaning tool might not be entirely efficient, as this method is still in its developmental stage. Apart from conducting investigations for various combinations of other parameters coupled with generation of micro-bubbles to control membrane bio-fouling, this project aims to perform an in-situ cultivation of Staphylococcus Aureus cells to simulate real-life conditions of bio-fouling. Through crystal violet and SEM image analysis, it was observed that the Staphylococcus Aureus biofilm attached better to the polystyrene surface than to the glass surface after incubation for